Financial literacy and Financial Planning Analysis of Generation Z in Sintang Regency on the Risk of Financial Fraud - Joko Susilo; Yasir Hudzaifah (Utan Kayu Publishing, 2025)
This research intends to examine the impact of financial literacy and financial planning on the likelihood of financial fraud among Generation Z in Sintang Regency. The method employed is Partial Least Squares Structural Equation Modeling (PLS-SEM) featuring three primary constructs: financial literacy, financial planning, and risk of financial fraud. The testing results for the outer model indicated that all metrics satisfy the requirements for validity and reliability. The R-square value of 0.946 shows that financial literacy and financial planning account for 94.6% of the variation in the risk of financial fraud. The hypothesis test indicated that financial literacy (? = 0.528; p 0.001) along with financial planning